SOSIALISASI SERTIFIKASI HALAL GRATIS (SEHATI) PADA PELAKU UMKM KECAMATAN BANGILAN TUBAN - Awaludin Ridwan; Afsah Indah Maulidah (Universitas YPPI Rembang, 2024)
This community service aims to increase consumer confidence in MSME MSME products in Bangilan District, Tuban Regency through socialization of the halal certification program. The service method applied is service learning, where service participants play an active role in providing understanding to MSME players about the importance of halal certification. The main objective is to involve participants in interactive and participatory learning, so that they can directly understand the positive impact of the halal certification program on increasing consumer confidence which has an impact on income. The results of the service show that MSME participants are interested in taking part in the process of obtaining halal certification, improving product quality and increasing consumer confidence. Thus, it is hoped that this service can make a positive contribution to the development of MSMEs in Sidokumpul Village, Bangilan District, Tuban Regency by improving halal principles so that it can support the BPJPH program to bring in MSME actors in 2024.Keywords: MSME, Halal Label, Satisfaction